Sagittal Imbalance Does Not Influence Cup Anteversion in Total Hip Arthroplasty Dislocations. Issue 1 (February 2019) - Haws, Brittany E.; Khechen, Benjamin; Patel, Dil V.; Louie, Philip K.; Iyer, Sravisht; Cardinal, Kaitlyn L.; Guntin, Jordan A.; Singh, Kern
Abstract : Study Design: Retrospective Cohort. Summary of Background Data: Studies have shown that lumbar fusion procedures are associated with an increased risk of total hip arthroplasty (THA) dislocation. Some have speculated that the increased risk of dislocation is caused by mispositioning of the acetabular component because of spinal sagittal imbalance. Unfortunately, the exact relationship between spinal sagittal balance and cup orientation is unknown. Objective: The objective of this study was to investigate the effect of spinal sagittal alignment on cup anteversion in THA dislocation. Methods: Patients that suffered a THA dislocation were retrospectively identified. Cross-table lateral hip radiographs were used to measure cup anteversion with normal acetabular anteversion defined as 15±10 degrees. Lateral lumbar spine radiographs were used to measure lumbar lordosis (LL), pelvic incidence (PI), pelvic tilt, and sacral slope. Normal sagittal balance was defined as a PI-LL difference of <10 degrees. The association between sagittal balance and THA characteristics was assessed using Pearson correlation coefficient, χ 2 analysis, and independent t tests. Results: A total of 29 patients had full radiographic imaging. Among these patients, 62.1% dislocated following a primary THA and 37.9% following a revision THA. Abnormal spinal sagittal balance was identified in 20 patients (69.0%). Eight (27.6%) patients had undergone spinal fusion prior to THA. Abnormal cup anteversion was demonstrated in 51.7% of all patients. Presence of a spinal fusion was not associated with cup anteversion, sagittal balance, or time to dislocation. Sagittal balance was not associated with direction of dislocation, time to dislocation, or cup anteversion. Conclusions: A majority of patients with a THA dislocation demonstrated abnormal sagittal balance. However, sagittal balance was not associated with acetabular cup anteversion. As such, the relationship between spinal deformity and dislocation rates after THA may not be because of inaccurate cup orientation.